2003
DOI: 10.2116/analsci.19.181
|View full text |Cite
|
Sign up to set email alerts
|

Design of Peptide that Recognizes Double-Stranded DNA

Abstract: A novel molecular tool for double-stranded (ds) DNA detection using synthetic peptide is described. The peptide was designed based on the DNA binding domain of the λ phage CRO repressor (CRO). The designed peptides contain helixturn-helix (HTH), which is DNA binding motif. A cyclic peptide and a mutant peptide based on CRO were also designed, and the resulting affinity for dsDNA was increased. Furthermore, native amino acids of the peptide were replaced with arginine to increase the affinity for dsDNA. The aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For example, two of the invariant residues, G4 and R11, are located within the predicted DNA-binding domain. While the role of glycine has not been well studied, structural analysis of other XRE-type helix-turn-helix domains has revealed that arginine in this position contributes to the stability of the DNA-protein complex through formation of a fold-stabilizing salt bridge with a conserved glutamic acid residue (22) or side chain contacts with phosphate groups in target DNA (11,(36)(37)(38). Invariant tryptophan residues are often involved in protein-protein interactions (19), and W142 may localize to the interface of a critical RopB-protein complex.…”
Section: Vol 189 2007 Notes 653mentioning
confidence: 99%
“…For example, two of the invariant residues, G4 and R11, are located within the predicted DNA-binding domain. While the role of glycine has not been well studied, structural analysis of other XRE-type helix-turn-helix domains has revealed that arginine in this position contributes to the stability of the DNA-protein complex through formation of a fold-stabilizing salt bridge with a conserved glutamic acid residue (22) or side chain contacts with phosphate groups in target DNA (11,(36)(37)(38). Invariant tryptophan residues are often involved in protein-protein interactions (19), and W142 may localize to the interface of a critical RopB-protein complex.…”
Section: Vol 189 2007 Notes 653mentioning
confidence: 99%
“…At present there are several reviews [20,21,22,23] and a book [24] summarizing antibody engineering, including the phage display method. Using the phage display method, double-stranded DNA (dsDNA) recognizing peptide was recently designed [25].…”
Section: Antibodies and Their Recognition Elementsmentioning
confidence: 99%